A novel approach using metabolomics coupled with hematological and biochemical parameters to explain the enriching-blood effect and mechanism of unprocessed Angelica sinensis and its 4 kinds of processed products. (30th January 2018) - Ji, Peng; Wei, Yanming; Hua, Yongli; Zhang, Xiaosong; Yao, Wanling; Ma, Qi; Yuan, Ziwen; Wen, Yanqiao; Yang, Chaoxue
Abstract: Ethnopharmacological relevance: Angelica sinensis (AS), root of Angelica sinensis (Oliv.) Diels, an important kind of Chinese traditional herbal medicine, has been used for women to enrich the blood for thousands of years. It is mainly distributed in Gansu province of China. According to Traditional Chinese medicine usage, unprocessed AS (UAS) and its 4 kinds of processed products (ASs) are all used to treat different diseases or syndromes. The difference among the enriching-blood effects of ASs is unclear. And their exact mechanisms of enriching the blood are not fully understood. Aim of the study: In this study, our aim is to compare the enriching-blood effect and explain the related mechanism of ASs, to lay the foundation for the blood deficiency diagnosis and the rational use of ASs in the clinic. Materials and methods: ASs were used to intervene the blood deficiency syndrome model mice induced by acetyl phenylhydrazine (APH) and cyclophosphamide (CTX). A novel approach using metabolomics coupled with hematological and biochemical parameters to explain the enriching-blood effect and mechanism of ASs was established. The blood routine examination, ATPase, glucose-6-phosphate dehydrogenase, methemoglobin, glutathion peroxidase, glutathione reductase, and erythropoietin were measured. Two biofluids (plasma and urine) obtained from mice were analyzed with GC-MS. Distinct changes in metabolite patterns of the two biofluids after mice were induced by APH and CTX, and mice were intervened with ASs were analyzed using partial least squares-discriminant analysis. Potential biomarkers were found using a novel method including variable importance in the projection (VIP) >1.0, volcano plot analysis, and significance analysis of microarray. Results: The results of hematological, biochemical parameters and the integrated metabolomics all showed the blood deficiency syndrome model was built successfully, ASs exhibited different degree of enriching-blood effect, and AS pached with alcohol (AAS) exhibited the best enriching-blood effect. 16 metabolites in the plasma and 8 metabolites in the urine were considered as the potential biomarkers. These metabolites were involved in 7 metabolic pathways which were concerned with the different enriching-blood effect mechanisms of ASs. The correlation analysis results confirmed L-Valine (plasma), Linoleic acid (urine), L-Aspartic acid (urine) and Cholesterol (urine) were strong positive or negative associated with biochemical indicators. Conclusions: The enriching-blood effects of ASs are different. The pathological mechanisms of blood deficiency syndrome and the enriching-blood effect mechanism of ASs are involved in 7 metabolic pathways. L-Valine (plasma), Linoleic acid (urine), L-Aspartic acid (urine), Cholesterol (urine) are four important biomarkers being related to the enriching-blood effect of ASs. The combination of VIP, volcano plot analysis and significance analysis of microarray is suitable for screening biomarkers in metabolomics study. They can lay the foundation for clinical practice. Graphical abstract: